SPECIAL FEATURES OF INDIVIDUAL LEARNING SYSTEMS FROM THE WORLDVIEW PERSPECTIVE - S. A. Kononenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
In the article, it is noted that, as of today, sciences that study human learning behavior have spawned a great number of various theoretical approaches each offering its own view on how the learning process takes place, what factors and to what extent affect this process. There is, nevertheless, a consensus among scientists that different people gravitate to their own preferable individual learning styles and that educational process is more effective when teachers adapt their teaching methods and techniques to their students' individual learning styles. Teachers have difficulty orienting themselves among a vast variety of theories and deciding which type of learning is more appropriate for each specific student or group and which method or type of teaching to use in the work with them. It is suggested that the psychological construct of "worldview" enables teachers to develop a viable approach to establishing the guidelines and criteria for making such a decision. In the article, a brief overview of the existing paradigms and theories as well as of the corresponding types of learning is provided; the conceptual foundations of modern approaches to the study of worldviews are delineated; a worldview approach to systemization of types of learning and their application based on C. Graves's theory is put forward.